Indentifikasi Faktor-faktor Pemilihan Metode Persalinan Sectio Caesarea di Rumah Sakit Pertamina Tanjung - Prasetyani, Indri Yayi; Yunita, Laurensia; Nuwindry, Iwan (Quantum Wellness : Jurnal Ilmu Kesehatan, 2024)
Caesarean section is a surgical procedure that involves making an incision on the front wall of the uterus to aid the birthing process. Objective: to determine the identification of factors for selecting the Sectio Caesarea delivery method at Pertamina Tanjung Hospital. Method: Quantitative descriptive research with a cross sectional approach, with a total sampling technique of 30 respondents, using a checklist. Results: The most indications for caesarean section delivery were indications of premature rupture of membranes > 24 hours as many as 5 (16.7%) and the least indications were asthma, CPD + hypertension in pregnancy, fatal distress, fetal distress, hypertension in pregnancy, long 1st stage with fatal distress, prolonged second stage with fetal distress, breech position, PEB and placenta previa were 1 (3.3%) each. The mother's delivery method was most commonly found to be Cito, 18 (60%). Maternal parity had the highest number of unsafe parities at 17 respondents (54%). The mother's age was found to be the most non-risk age by 16 respondents (53.3%). The health insurance used by mothers was found to be mostly used by 28 respondents (93.3%). Conclusion: Indications for cesarean delivery are indications of previous CS, safe parity, maternal age is not at risk, and using health insurance. Most parities are unsafe with indications of premature rupture of membranes > 24 hours.